2001
DOI: 10.1046/j.1365-2036.2001.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mucosal fibrinolytic activity in gastroduodenal ulcer haemorrhage and the beneficial effect of acid suppression

Abstract: Background: The high mortality rate in patients with upper gastrointestinal bleeding appears to be particularly related to re‐bleeding. The haemostatic mechanisms that may influence the re‐bleeding of ulcers are largely unknown. Aim: We studied and analysed fibrinolytic activity in bleeding ulcer patients and the effect of acid suppression on this activity. Methods: Fibrinolytic activity was analysed in mucosal biopsies from 29 bleeding gastroduodenal ulcer patients and six controls. We analysed levels of D‐Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Platelet aggregation is impaired at acidic gastric pH [33]. In addition, mucosal fibrinolytic activity following peptic ulcer hemorrhage may be mitigated by effective acid suppression [34]. Raising the gastric pH is thought to be the central mechanism by which histamine (H2) antagonists and PPIs promote ulcer healing and reduce re-bleeding rates.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation is impaired at acidic gastric pH [33]. In addition, mucosal fibrinolytic activity following peptic ulcer hemorrhage may be mitigated by effective acid suppression [34]. Raising the gastric pH is thought to be the central mechanism by which histamine (H2) antagonists and PPIs promote ulcer healing and reduce re-bleeding rates.…”
Section: Discussionmentioning
confidence: 99%
“…5 In nonsurgical management of gastrointestinal ulcer bleeding, D-dimer level reflects fibrinolytic area on ulcer tissue and medication decreases D-dimer level. 6 We wished to ascertain the standard range of D-dimer level associated with each type of gynecologic surgery. We are expecting a D-dimer level beyond the standard …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that gastric pH above 6 promotes aggregation of platelets, inhibits activation of pepsin and prevents clot dissolution [13-15]. The levels of gastric pH achieved are not different in oral or intravenous administration.…”
Section: Pharmaceutical Treatmentmentioning
confidence: 96%